2014
DOI: 10.1016/j.combustflame.2013.11.016
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamic detonation parameters in acetylene–oxygen mixtures with varying amount of argon dilution

Abstract: In this investigation, the dynamic detonation parameters for stoichiometric acetylene-oxygen mixtures diluted with varying amount of argon are measured and analyzed. The experimental results show that the critical tube diameter and the critical energy for direct initiation of spherical detonations increase with the increase of argon dilution. The scaling behavior between the critical tube diameter dc and the detonation cell size λ as well as the critical direct initiation energy Ec is systematically studied wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Consequently, its research is crucial in the design of ODWE. Recent studies [28][29][30] on normal detonation initiation have demonstrated that both aerodynamic and mixture thermodynamic properties greatly influence the initiation of detonation. However, a deep knowledge of the oblique structure found in ODWE is still lacking and must be fully addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, its research is crucial in the design of ODWE. Recent studies [28][29][30] on normal detonation initiation have demonstrated that both aerodynamic and mixture thermodynamic properties greatly influence the initiation of detonation. However, a deep knowledge of the oblique structure found in ODWE is still lacking and must be fully addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Here the induction length is determined as the length of the thermally neutral period in the ZND structure. It is defined as the distance from the leading shock to the maximum temperature gradient in the ZND temperature profile as used in previous studies [19,29,30]. As can be seen from Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Various levels of description of acetylene ignition and detonation chemistry were generated for computational and theoretical studies of high-temperature ignition and detonation behavior of fuels that contain or produce appreciable amounts of acetylene. These have mostly been validated and optimized for detonation simulations in gaseous hydrocarbon mixtures, which are also verified in our recent investigation [29] for studying the effect of varying argon dilution on the dynamic parameters of acetylene-oxygen-argon detonations.…”
Section: Discussionmentioning
confidence: 99%
“…High-voltage electric spark was used to supply ignition energy as in previous studies [39][40][41][42][43][44][45][46]. The igniter was mounted at the center of the spherical bomb and a spark energy of 10 J, estimated from 1/2 CU 2 (''C'' and ''U'' refer the capacitance and voltage, respectively.…”
Section: Methodsmentioning
confidence: 99%